An Explorative Study Comparing the Knowledge of Tobacco Use and Tobacco Cessation Program among School Going Boys and Girls: A Study in Ahmedabad District in Western India - Bhatt, Meghna; Hedov, Gerth; Modi, Bhavesh (National Journal of Community Medicine, 2018)
Introduction: Awareness of health risks of tobacco use, and ado- lescents’ behavior are strongly associated with adolescents’ know- ledge and perceptions towards tobacco use. There are only a few studies being conducted that assess school going boys’ and girls’ tobacco-related health knowledge, and their awareness related to tobacco control programmes. Method: A questioner base cross-sectional study with 276 stu- dents had been conducted from four different schools (2 private and 2 governments) in Ahmedabad district, Gujarat, India. The results include from the group comparison (hypothesis testing) between the boys and girls. Results: More than two thirds of boys’ and girls’ participants agreed tobacco use (also in all forms) is harmful to the body. More than one third boys and one quarter girls believed that media plays an important role in promoting anti-tobacco messages. Around 50 % of the girls preferred strict anti-tobacco laws and policies. More than two thirds of the boys and girls in the study sample had no knowledge of any organizations or programs that assisted individuals to get rid of the tobacco habit. Conclusion: Promoting school and community-based intervention programs and reviewing of the existing anti-tobacco policies could prove to be beneficial in curbing the tobacco consumption habit in adolescents.